Micro-level practices to adapt to climate change for African small-scale farmers: A review of selected literature - Below, Till; Artner, Astrid; Siebert, Rosemarie; Sieber, Stefan (International Food Policy Research Institute, 2010)
This paper discusses micro-level practices for adapting to climate change that are available to small-scale farmers in Africa. The analysis is based on a review of 17 studies about practices that boost small-scale farmers' resilience or reduce their vulnerability to observed or expected changes in climate; it includes data from more than 16 countries in Africa, the Americas, Europe, and Asia. The review shows that African smallholders are already using a wide variety of creative practices to deal with climate risks; these can be further adjusted to the challenge of climate change by planned adaptation programs. We found 104 different practices relevant to climate change adaptation and organized them in five categories: farm management and technology; farm financial management; diversification on and beyond the farm; government interventions in infrastructure, health, and risk reduction; and knowledge management, networks, and governance. We conclude that adaptation policies should complement farmers' autonomous response to climate change through the development of new drought-resistant varieties and improved weather forecasts, the provision of financial services, improvement of rural transportation infrastructure, investments in public healthcare and public welfare programs, and policies that improve local governance and coordinate donor activities.